ANALISIS KECENDERUNGAN PENELITIAN SKRIPSI MAHASISWA PGMI SEBAGAI REVITALISASI BIDANG KEAHLIAN GURU MI (SUATU PENDEKATAN META-ANALISIS) - Mila Hasanah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2014)
Students tend to have a dependence on thesis research issue that has been investigated earlier generation. This dependence if left unchecked will result in less mastered the skills to examine other research themes and less diverse issues of research and limited research themes so that students understand the difficulty of completing the thesis and the resulting increase in student study period. This study aims to identify, analyze and map the results of educational research student during the period of 5 years, from 2009 until July 2013. Study was conducted with the meta-analysis approach and a case study (case study research) with using the instrumental case study design. Based on analysis of student thesis research in primary, concluded: [1] thesis research issues of the most widely studied by students majoring in primary education during the period of 5 years, in terms of aspects: first; Both thesis research subjects; Aspects of the subject / Third thesis research material; Methods / type of study Fourth; Issues in education research thesis [2] thesis research issues that allows for further researched by the students of primary education in the coming period.